On Collective Rationality and a Generalized Impossibility Theorem - Fishburn, Peter C. (Review of Economic Studies, 1974)
Journal Article On Collective Rationality and a Generalized Impossibility Theorem Get access Peter C. Fishburn Peter C. Fishburn The Pennsylvania State University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 4, October 1974, Pages 445–457, https://doi.org/10.2307/2296696 Published: 01 October 1974